Clinical features of osteoarthritis in patients with metabolic syndrome - L V Vasilyeva (Терапевтический архив, 2017)
Aim. To estimate clinical and laboratory parameters in patients with osteoarthritis (OA) and in those with OA and metabolic syndrome (MS). Subjects and methods. 164 patients with OA were examined and divided into 2 groups of 82 people: a study group (patients with MS) and a control one (those without MS). OA was defined according to the diagnostic criteria described by R.D. Althmann (1995). MS was identified based on the criteria developed by the International Diabetes Federation (2005). The location of affected and swollen joints was determined according to the Richie index; the intensity of pain syndrome was measured by a visual analogue scale at rest and on movement; the WOMAC and Lequesne indexes were estimated in the patients. Erythrocyte sedimentation rate and C-reactive protein and tumor necrosis factor-α levels were determined from laboratory data. Results. In the MS group, the frequency of joint injuries at various sites, the prevalence of synovitis, and the intensity of pain and inflammation were significantly higher than in the non-MS group. Conclusion. The negative impact of MS on the clinical picture of OA can be inferred by the findings.